ISLAMIC BOARDING SCHOOLS AND THE THEORY OF SOCIAL CHANGE IN SOUTHEAST ASIA - Mundzier Suparta (STAI ALHIKMAH Jakarta, 2024)
AbstractThis article wants to analyze the relationship between social change theory and Islamic boarding schools in Southeast Asia. With a qualitative analysis method, in this article it is revealed that the pattern of Islamic Boarding School Education is adopted in several countries in Southeast Asia, especially in Malaysia, Southern Thailand and the Southern Philippines. Some scholars in Southeast Asia studied a lot in Islamic boarding schools in Indonesia, and developed a similar pattern after graduating from Indonesia. Islamic boarding schools in Southern Thailand still maintain the tradition of reciting with pegon or Jawi letters in Pondok and Madrasah. They form Muslim leaders in Southern Thailand, Malaysia and the Philippines as well as Muslim communities in other Southeast Asian communities. In the case of changes in Islamic boarding schools in Southeast Asia, both changes due to elements from within and from outside, the role of kyai as an actor of change occupies a very central position.AbstrakArtikel ini ingin menganalisis keterkaitan teori perubahan sosial dengan pesantren di asia Tenggara. Dengan metode analisis kualitatif, dalam artikel ini terungkap bahwa pola Pendidikan Pesantren diadopsi di beberapa negara di Asia Tenggara, khususnya di Malaysia, Thailand Selatan dan Filipina Selatan. Beberapa Ulama di Asia Tenggara banyak belajar di pesantren-pesantren di Indonesia, dan membangun pola yang mirip setelah lulus dari Indonesia. Pesantren di Thailand Selatan hingga saat ini masih menjaga tradisi mengaji dengan huruf pegon atau huruf jawi di Pondok dan Madrasah. Mereka membentuk pemimpin Muslim di Thailand Selatan, Malaysia dan Filipina serta komunitas Muslim di Asia Tenggara lainnya. Dalam kasus perubahan di pondok pesantren di Asia Tenggara, baik perubahan karena unsur dari dalam maupun dari luar, peran kyai sebagai aktor perubahan menempati posisi yang sangat sentral.